Exchange rates, international trade and growth: Re-evaluation of underevaluation - Maria V. Sokolova (Graduate Institute of International and Development Studies, 2016)
This paper shows that a regional bias resulting from trade integration alters the transmission of a country's monetary policy by shifting the burden of the exchange rate adjustment towards the less integrated trading partners. I first develop a simple model which illustrates how a concentration of trade flows among regional trading partners affects the sensitivity of the trade balance to the terms-of-trade. In particular, the trade balance becomes less sensitive to the terms-of-trade vis-a-vis regional partners and more sensitive to the terms-of-trade vis-a-vis the other country. I then test the implication of the model using a panel of 133 countries between 1985 - 2010 that includes information on Regional Trade Agreements (RTA). I find that movements in the terms-of-trade vis-a-vis non-RTA members affect a countrys trade balance, while movements vis-a-vis RTA partners do not.
Keywords: F10; F13; F14; F15; F40; F41; F45; 330; trade balance; regional trade agreements; competitive depreciation; economic integration; terms-of-trade